[Students of color on Dexter Lawn] (1992)
Small group of about 8 students sitting on Dexter lawn. The students are in front of set of parallel bars used for gymnastics, as well as blue gymnastic mats. The Engineering West building in the background has a sign in a window that reads 'What's the rule?'